2002
DOI: 10.1007/bf02976940
|View full text |Cite
|
Sign up to set email alerts
|

The anti-fibrogenic effect of a pharmaceutical composition of [5-(2-Pyrazinyl)-4-methyl-1,2-dithiol-3-thione] (Oltipraz) and Dimethyl-4,4′-dimethoxy-5,6,5′,6′-dimethylene dioxybiphenyl-2,2′-dicarboxylate (DDB)

Abstract: Liver fibrosis is a prepathological state wherein damaged liver tissues in chronic liver diseases, such as hepatitis, are not repaired to normal tissues, but converted to fibrous tissue. 5-(2-Pyrazinyl)-4-methyl-1,2-dithiol-3-thione (oltipraz), a cancer chemopreventive agent, is effective against a wide variety of chemical carcinogens. Recently, we reported that oltipraz inhibits liver fibrogenesis (Kang et al., 2002). In the present study, the effects of oltipraz in combination with dimethyl-4,4'-dimethoxy-5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the present work, treatment of rats with DDB or silymarin along with CCl 4 resulted in diminution of cirrhosis and fibrosis. Other researchers reported that dimethylnitrosamine (DMN)-induced liver fibrogenesis, however, was not reduced by DDB [28]. In rats treated with CCl 4 , Favari and Perez-Alvarez [46] reported a 55% reduction in liver collagen by silymarin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, treatment of rats with DDB or silymarin along with CCl 4 resulted in diminution of cirrhosis and fibrosis. Other researchers reported that dimethylnitrosamine (DMN)-induced liver fibrogenesis, however, was not reduced by DDB [28]. In rats treated with CCl 4 , Favari and Perez-Alvarez [46] reported a 55% reduction in liver collagen by silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to note that both DDB and silymarin possess important anti-inflammatory properties, which are likely to be of relevance to their hepatoprotective and antifibrotic effects. Kang et al [28] suggested that DDB decreases liver cell injury and inflammation through inhibition of nuclear factor-kB. In an immune-mediated liver injury caused by concanavalin A in mice, the elevation of serum TNF-alpha and liver TNF-alpha mRNA expression 2 h after Con A injection was decreased by the prior administration of DDB [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, DDB is a promising approach as compared to Schisandra chinensis and its active compounds for clinical application. In addition, DDB effectively ameliorated serum aminotransferase, oxidative stress-associated parameters, and liver fibrosis in previous studies [18][19][20]. Owing to its quick effects, low price and easy synthesis by using gallic acid, DDB has widely been applied as a hepatoprotective and antiviral therapeutic agent to cure various liver disorders in Asian countries, such as south Korea, China, and Indonesia [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Oltipraz (oltipraz powder was suspended in 40% PEG 400, 50 mg kg ¡1 , nˆ7), DDB (DDB powder was also suspended in 40% PEG 400, 10 mg kg ¡1 , nˆ7) and oltipraz (50 mg kg ¡1 ) plus DDB (10 mg kg ¡1 ) (nˆ9) were administered via the jugular vein over 1 min (total injection volume was approximately 0.6 mL). It has been reported from our laboratories (Kang et al 2002b) that an improved liver antifibrotic effect was observed when oltipraz (25 mg kg ¡1 ) plus DDB (5 mg kg ¡1 ) was administered orally to rats. Because of the assay sensitivity of DDB, the dose of DDB and oltipraz was increased twice in the present study.…”
Section: Intravenous Administrationmentioning
confidence: 97%